PENGARUH MEDIA PEMBELAJARAN VISUAL BERBASIS QUIVER TERHADAP HASIL BELAJAR MEWARNAI SISWA KELAS V SDN 060843 MEDAN BARAT : Penelitian Kuantitatif - Ratih Ratih Ayunda; Putra Afriadi; Nurmayani; Tiarnita Maria Sarjani Br. Siregar; Sri Mustika Aulia (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
The study was conducted with the aim of determining the effect of Quiver-based visual learning media on the learning outcomes of fifth grade students of SDN 060843 Medan Barat. The study population consisted of all students in grades V-2 and V-4 of SDN 060843 totaling 50 students. The research sample was the total number of students in grades V-2 and V-4 of SDN 060843 totaling 50 students taken using total sampling. The data collection technique used in this study was by using 4 data in the form of observation data, interviews, written tests and documentation. The results of the study showed that there was an effect on the learning outcomes of fifth grade students of SDN 060843 after using Quiver-based visual learning media after conducting normality tests and t-tests on the research data. Based on the findings of the research results, it is recommended for researchers and educators to be able to optimize learning media by utilizing technology, especially those based on Augmented Reality (AR).